Controlling the viscosities of antibody solutions through control of their binding sites - Kastelic, Miha (J Mol Liq, 2017)
For biotechnological drugs, it is desirable to formulate antibody solutions with low viscosities. We go beyond previous colloid theories in treating protein–protein self–association of molecules that are antibody–shaped and flexible and have spatially specific binding sites. We consider interactions either through fragment antigen (Fab–Fab) or fragment crystalizable (Fab–Fc) binding. Wertheim's theory is adapted to compute the cluster–size distributions, viscosities, second virial coefficients, and Huggins coefficients, as functions of antibody concentration. We find that the aggregation properties of concentrated solutions can be anticipated from simpler–to–measure dilute solutions. A principal finding is that aggregation is controllable, in principle, through modifying the antibody itself, and not just the solution it is dissolved in. In particular: (i) monospecific antibodies having two identical Fab arms can form linear chains with intermediate viscosities. (ii) Bispecific antibodies having different Fab arms can, in some cases, only dimerize, having low viscosities. (iii) Arm–to–Fc binding allows for three binding partners, leading to networks and high viscosities.